(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This research explores the interplay of Surrealism and Existentialism in Franz Kafka’s novella, "The Metamorphosis." Kafka’s narrative is renowned for its surreal depiction of a man, Gregor Samsa, who awakens to find himself transformed into a gigantic insect. This transformation serves as a powerful metaphor for the existential themes of alienation, identity crisis, and the absurdity of human existence. Through a surreal lens, Kafka vividly portrays Gregor’s internal and external struggles, emphasizing the dissonance between his human consciousness and his monstrous form. This study has beenemploy a qualitative approach, focus on literary analysis to explore the themes of surrealism and existentialism in Kafka’s novella. The Research delves into how Kafka employs surreal elements to magnify existential concerns, such as the meaningless routines of daily life, the erosion of personal relationships, and the quest for purpose in an indifferent world. By analyzing key scenes and symbols in "The Metamorphosis," the research highlights the intricate fusion of surrealism and existentialism, offering a deeper understanding of Kafka’s commentary on the human condition. Through this dual philosophical framework, Kafka’s work is positioned as a profound critique of modern existence, reflecting the pervasive anxieties of his time and resonating with contemporary readers.